A Constructivist Analysis of Liberia’s Ebola Response - Michlyne Nyenegahn Williams (European Scientific Journal, ESJ, 2025)
This article examines how Liberia established its sovereignty, legitimacy, and international identity during the Ebola crisis of 2014-2015. While much existing research focuses on institutional weaknesses and material dependence, this study employs a constructivist qualitative methodology that combines discourse analysis and content analysis of governmental communications, United Nations resolutions, international reports, and international media coverage. The analysis focuses on identifying patterns in state rhetoric, norm alignment, and engagement strategies with international actors. The findings indicate that Liberia’s response was influenced not only by material constraints but also by international efforts to align with international norms, construct a credible national identity, and assert legitimacy in the global arena. By analyzing Liberia’s experience, this article contributes to discussions on global health governance, African statehood, and the application of constructivist theory in international relations.